014 AVXS-101 gene-replacement therapy (GRT) in presymptomatic spinal muscular atrophy (SMA): study update. (29th July 2019) - Farrar, Michelle; Swoboda, Kathryn J; Schultz, Meredith; McMillan, Hugh; Parsons, Julie; Alexander, Ian E; Kernbauer, Elaine; Farrow, Marcia; Ogrinc, Francis G; Feltner, Douglas E; McGill, Bryan E; Spector, Sidney A; et al.
Abstract : Introduction: SMA is a neurodegenerative disease caused by biallelic deletion/mutation of the survival motor neuron 1 gene ( SMN1 ). Copies of a similar gene ( SMN2 ) modify disease severity. In a phase 1 study, SMN GRT onasemnogene abeparvovec (AVXS-101) improved outcomes of symptomatic SMA patients with two SMN2 copies (2x SMN2 ) dosed ≤6 months. Because motor neuron loss can be insidious and disease progression is rapid, early intervention is critical. This study evaluates AVXS-101 in presymptomatic SMA newborns. Methods: SPR1NT is a multicenter, open-label, phase 3 study (NCT03505099 ) enrolling ≥27 SMA patients with 2–3x SMN2 . Asymptomatic infants ≤6 weeks receive a one-time intravenous AVXS-101 infusion (1.1×10 14 vg/kg). Safety and efficacy are assessed through study end (18 [2x SMN2 ] or 24 months [3x SMN2 ]). Primary outcomes: independent sitting for ≥30 seconds (18 months [2x SMN2 ]) or assisted standing (24 months [3x SMN2 ]). Results: From April–September 2018, 7 infants received AVXS-101 (4 female; 6 with 2x SMN2 ) at ages 8–37 days. Mean baseline Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders (CHOP-INTEND) score was 41.7 (n=6), which increased by 6.8, 11.0, 18.0, and 22.5 points at day 14 (n=4), month 1 (n=3), 2 (n=3), and 3 (n=2). As of January 31, 2019, 15 asymptomatic infants have been enrolled in SPR1NT and dosed with AVXS-101. Updated data available at the time of the congress will be presented. Conclusions: Preliminary data from SPR1NT show rapid motor function improvements in presymptomatic SMA patients.